A New Algorithm for Protection of Small Scale Synchronous Generators Against Transient Instability - Zinat Khosravi; Alireza Saffarian (Institute of Advanced Engineering and Science, 2015)
Today, installation of small generators has been increased because of their considerable benefits in distribution systems in distributed generation. One of the most important problems for transient stability is the effects of the faults of system. Small scale generators have low constant inertia and protection relays have slow performance in distribution systems. Therefore transient instability is a probable phenomenon for the systems with these generators. In this paper, dynamic response of generator has been studied in different fault conditions and then by introducing the concept of